Successful identification of Granulicatella adiacens in postoperative acute infectious endophthalmitis using a bacterial 16S ribosomal RNA gene-sequencing platform with MinION™: A case report - Masato Ishino; Masatoshi Omi; Kaoru Araki-Sasaki; Shimpei Oba; Haruhiko Yamada; Yoshiyuki Matsuo; Kiichi Hirota; Kanji Takahashi (American Journal of Ophthalmology Case Reports, 2022)
Purpose: To evaluate the efficacy of identifying the bacteria by aqueous sampling and vitreous sampling in postoperative infectious endophthalmitis using 16S ribosomal RNA (rRNA) gene analysis with a nanopore sequencer (MinION™). Observation: A 55-year-old woman who underwent cataract surgery at an ophthalmology clinic 18 days ago was referred to our hospital for suspected endophthalmitis. She had light perception visual acuity in her right eye; however, the eye was severely inflamed, with a hypopyon and a fibrinous membrane in the anterior chamber. The fundus was not visible because of vitreous opacity on a B-scan image. Based on the diagnosis of postoperative acute infectious endophthalmitis, we performed a vitrectomy, intraocular lens extraction, and silicone oil tamponade. On postoperative day 14, the inflammation resolved. An aqueous sample was collected before surgical treatment, and the vitreous sample was collected during the operation. Both samples underwent 16S rRNA gene analysis with a nanopore sequencer MinION™ to identify the causative organism. Conclusions and Importance: In the aqueous humor, Granulicatella adiacens and Cutibacterium acnes were identified before the operation, while only Granulicatella adiacens was detected in the vitreous sample after the operation. Although the aqueous humor sample might contain commensal bacteria, it could provide a predictable result before the operation. It can also provide a substitute for a vitreous sample to allow earlier identification of the causative organism.